The initial stage of the study of spiders (Aranei) in Grabove ravine (Piatikhatkyi district, Dnepropetrovsk region) - Prokopenko, E. V.; Zhukov, A. V. (Acta Biologica Sibirica, 2018)
Linden-hornbeam oak forests in Grabove ravine can be regarded as the easternmost outpost of the massive distribution of the hornbeam in Ukraine. The material for this paper was collected in Belenschina Village (Piatikhatskyi District, Dnepropetrovsk Region) since May to June 2009 using pitfall traps. Glass jars of 0,5 liter volume containing 2 % formalin served as pitfall traps. There are 524 trap-days were spent and 402 specimens were collected. A total 18 spider species from 9 families are recorded. This result does not reflect the actual species richness in Grabove ravine. There is a need to take further research to complete the spider species list. Maximal species richness and abundance characterize families Lycosidae (5 species, 84,1 % specimens) and Thomisidae (3 species, 7,3 % specimens). The largest number of spider species was recorded in the lower third of the southern slope (11 species), the largest value of dynamic density was in the middle third of the southern slope (154,4 specimens/100 trap-days). The minimal species richness (5 species) was found in the middle third of the northern slope. The lowest values of dynamic density were recorded in the lower third of the northern slope (39,4 specimens/100 trap-days).